2012
DOI: 10.4028/www.scientific.net/amr.445.607
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Rapid Prototyped Artificial Bone Scaffold Structures

Abstract: Fluid flow through a bone scaffold structure is an important factor in its ability to build up a living tissue. Permeability is often used as a measure of a structure’s ability to allow for flow of nutrients and waste products related to the growth of new tissue. These structures also need to meet conflicting mechanical strength requirements to allow for load bearing. In this work, the effect of different bone structure morphologies on permeability were examined both numerically and experimentally. Cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In the meantime, as expected, higher permeabilities were recorded for larger pore sizes and porosity ( Figure 8 ). These results are quite consistent with S. Gómez' study [ 32 ], and previous numerical calculations also had confirmed experimental results which indicated that permeability increased with increasing pore sizes and porosity [ 41 ]. However, with the increasing of volume, surface area, and specific surface area, average permeability seemed to be decreased.…”
Section: Discussionsupporting
confidence: 91%
“…In the meantime, as expected, higher permeabilities were recorded for larger pore sizes and porosity ( Figure 8 ). These results are quite consistent with S. Gómez' study [ 32 ], and previous numerical calculations also had confirmed experimental results which indicated that permeability increased with increasing pore sizes and porosity [ 41 ]. However, with the increasing of volume, surface area, and specific surface area, average permeability seemed to be decreased.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of the CGCaP scaffold and PCL-CGCaP composite, a high degree of specific surface area was reflected in the significantly lower permeability compared to the PCL support alone (Figure 4). The relatively lower specific surface area and resultant increased permeability in the 3D printed PCL construct has been previously attributed to limitations in feature size (mm-scale, rather than micron-scale, pores) (Lipowiecki et al, 2014). The significance of specific surface area as a biomaterial design parameter has similarly been addressed (Harley and Gibson, 2008;O'Brien et al, 2007;O'Brien et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Permeability was measured as previously described (Lipowiecki et al, 2014;O'Brien et al, 2007;Weisgerber et al, 2013). Briefly, axial permeability was assessed with flow through using a custom polycarbonate rig and a constant pressure head (ΔP) of 26.7 cm of de-ionized water.…”
Section: Permeability Of Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we aimed to minimize the impact of pore size by designing the pores to be equivalent in size, and focus on the impact of pore geometry on cell behavior, a concept that has been much less studied. Trabecular bone has a macroporous structure, with open marrow space pores on the order of 1 mm in size [33]. Previous studies have shown that larger pore sizes (on the order of 1-3 mm) allow for greater interaction between cells and the underlying biomaterial, improving the osteogenic properties of the tissue and resulting in a thicker tissue formation along the material surface [34,35].…”
Section: Discussionmentioning
confidence: 99%